Explaining varying lobbying styles across the Atlantic: an empirical test of the cultural and institutional explanations. (22nd April 2016) - Hanegraaff, Marcel; Poletti, Arlo; Beyers, Jan
Abstract: There is consensus in the literature that policymaking in the United States (US) and Europe generates different lobbying styles. Two explanations for these differences have been developed so far. The first posits that distinct lobbying styles reflect different political cultures . The second attributes distinct lobbying styles to variation in the institutional context in which lobbyists operate. Studies that have analysed lobbying within the US and Europe and assessed the relative importance of these arguments are problematic because both explanations are consistent with observed differences in lobbying style. In this article, we circumvent problems of observational equivalence by focussing on European and American lobbyists who are active in a similar institutional venue – that is, international diplomatic conferences. Relying on evidence collected at World Trade Organization Ministerial Conferences and United Nation Climate Summits, we tested the relevance of alternative explanations for the variation in lobbying styles between European and American lobbyists. Our results give robust support to the institutional argument.